Pelatihan Penyusunan Lembar Kerja Peserta Didik Berbasis Masalah dan Proyek - Nurul Ratnawati; Neni Wahyuningtyas; Muhammad Mujtaba Habibi; Ferdinan Bashofi; Diana Anggita Nareswari (Jurnal Pemberdayaan Masyarakat, 2025)
This community service activity was motivated by the problem of the low quality of Student Worksheets (LKPD) used by teachers at SMP Negeri 16 Malang City. The LKPD in circulation are generally not in line with the characteristics of innovative learning models such as Problem Based Learning (PBL) and Project Based Learning (PjBL), so they are not optimal in supporting the development of 21st century skills. The purpose of this activity is to improve teachers' understanding of the PBL and PjBL models and the deep learning approach, train teachers in compiling LKPD based on these models with the help of live worksheet technology, and produce contextual and applicable LKPD. The method used is service learning through four stages: survey, preparation, implementation, and evaluation-follow-up. The results show that the training activities carried out using blended learning are able to significantly improve teachers' understanding, facilitate the preparation of LKPD that are in line with PBL and PjBL syntax, and encourage critical reflection through presentations and peer feedback. Evaluation through questionnaires showed a positive response from participants, especially in terms of material relevance and resource person competence.